Makna Dibalik Perilaku Umat Buddha Dalam Mengoleksi Amulet (Studi Kasus: Umat Buddha Di Vihāra Jakarta Dhammacakka Jaya dan Umat Buddha Di Vihāra Buddha Metta Arama) - Suwanto Suwanto (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The author looks at the habits of Buddhists at the Jakarta Dhammacakka Jaya Vihara and Metta Arama Buddhist Viharas who wear necklaces in the form of pendants, bracelets so that the authors can formulate research problems in this thesis, namely: 1). What is the meaning behind the behavior of Buddhists in collecting amulets? In writing this thesis, the researcher uses the research method used is a qualitative method. The results of this study are (1) that amulets are objects with various shapes, which can be in the form of pendants, bracelets, rings, which have different functions, purposes and benefits, adapted to certain conditions. (2) amulet is a cultural tradition that has different forms and is only a symbol not as a talisman. According to Buddhism, this amulet is not allowed because the Buddha said to avoid things that are believed to be auspicious, amulets (amulets for today) as a means of seeking life's necessities. The Buddha gave priority to developing the mind in order to become more virtuous and wise and to practice the Noble Eightfold Path in order to be free from Dukkha.